Depredacion en crías de venado cola blanca (Odocoileus virginianus texanus) por coyote (Canis latrans) en una Unidad de Manejo y aprovechamiento del Norte de Nuevo León, México - López Soto, Juan Homero; Badii, Mohammad H. (Instituto de Ecología, A.C., 2000)
Deer fawn predation was evaluated through the analysis of 1,117 coyote scats, which were collected in one-year period, from August 1997 to August 1998 at the UMA San Jose, Anahuac, Nuevo Leon, Mexico. Fawn mortality did not produce considerable impact on deer population. Moreover, in open areas, other wildlife management alternatives produce better results than the coyote control techniques